Association of risk factors for hypertension in a rural population of northern Perak - Loh, K.W.; Rani, F.; Chan, E.T.C.; Loh, H.Y.; Ng, C.W.; Moy, Foong Ming (2012)
Hypertension is a major public health problem in Malaysia. The National Health and Morbidity Survey 2006 showed the prevalence of hypertension among adults 30 years and above was 43. Therefore we attempted to examine the association of known modifiable and non-modifiable risk factors of hypertension. A survey was initiated among the rural population of Northern Perak. A total of 2025 respondents aged 30 years and above were recruited using a multi-stage sampling among five districts in Northern Perak. Hypertension was defined as self-reported hypertension and/or average of two blood pressure readings at single occasion with SBP â¥ 140mmHg or DBP â¥ 90 mmHg. Body mass index (BMI) was defined using the Asian criteria and IPAQ was used to evaluate physical activity. Body weight, height and blood pressure were obtained using standard procedures. In total, 1076 (54.9) respondents were found to be hypertensive. Significant associations (p <0.001) with hypertension were noted for increasing age, low physical activity, high BMI, no education background and positive family history of hypertension. The association between hypertension and each risk factor was investigated after adjusting for age, sex, ethnicity, education background, family history, BMI, physical activity, smoking and diet using Multiple Logistic Regression. Respondents who were obese had the odds of 3.69 (95 CI: 2.22-6.14) of having hypertension while those with positive family history had the odds of 1.96 (1.59-2.42) times for hypertension. A significant increase (p <0.001) in risk for hypertension was noted for age. Those with moderate physical activities were 1.40 (1.04-1.78) times more of having hypertension than those active. Poor diet score and smoking were not significantly associated with increased risk for hypertension. In conclusion, modifiable risk factors such as BMI and physical activity are important risk factors to target in reducing the risk for hypertension.